Alternative pretreatments of rice and tobacco wastes for the production of fermentable sugars - C. Curbelo-Hernández; E. Véliz-Lorenzo; José Ma. Ameneiros Martínez (Revista Facultad de Ingeniería Universidad de Antioquia, 2019)
The scarce oil supplies and the emissions of gases of greenhouse effect have caused the interest in production and utilization of lignocellulosic bioethanol. This can substitute partially or totally the fossil fuels. The stages of pretreatment and enzymatic hydrolysis are the most expensive. Different pretreatments have been studied for ethanol production from these materials. Their results depend on the method characteristics and on biomass used. The agroindustrial wastes present a composition with possibilities of being evaluated like raw material for bioethanol production. In the present research, the pretreatment stages with Ultrasound and Ozone are studied, in order to decrease the lignin content and to increase the performance of the fermentative sugars in the lignocellulosic wastes (rice hull and dark tobacco vein). In the first pretreatment procedure, time and waste type were studied and in the second stage, the ozone concentration, waste type and moisture content were the studied variables. A combined procedure was applied to the best preliminary results. It is demonstrated that a decrease in the lignin concentration and the structural transformation of the materials under consideration come true. The best results were gotten for the rice hulls.